Importance of Linguistics Diversity in Inclusive Education: A Study of District Lower Chitral Pakistan - Azmat Ullah; Dr. Assad us Samad (Research Journal of Psychology, 2025)
The study aims to investigate the importance of language diversity in inclusive education within the district Chitral. The study is quantitative in nature. The population is all the male and female students in district lower Chitral. Using simple random sampling techniques random sample of 300 participants (150 males and 150 females) selected for data collection. The collected data were fed into SPSS latest version 29 and analyzed. The findings revealed that 88% of the respondents experience challenges such as shyness, frustration, discouragement, and difficulty in understanding due to language barriers. Moreover, the study underscores the significance of inclusive education in various regions of Lower Chitral, where diverse languages are spoken. Notably, students who are not proficient in the national language often feel hesitant to participate in class. Based on the findings, the study recommends that teacher training is essential to equip educators with the skills to include students with diverse linguistic backgrounds. Additionally, it suggests that the curriculum should be designed to reflect the diverse cultural context, necessitating a fair and comprehensive approach to education.